2007
DOI: 10.1128/jvi.00691-07
|View full text |Cite
|
Sign up to set email alerts
|

Chemoimmunotherapy of Chronic Hepatitis B Virus Infection in the Woodchuck Model Overcomes Immunologic Tolerance and Restores T-Cell Responses to Pre-S and S Regions of the Viral Envelope Protein

Abstract: Treatment of chronic hepatitis B virus (HBV) infection could combine potent antiviral drugs and therapeuticvaccines to overcome immunological tolerance and induce the recovery phenotype to protect against disease progression. Conventional vaccination of woodchucks chronically infected with the woodchuck hepatitis virus (WHV) elicited differential T-cell response profiles depending on whether or not carriers were treated with the potent antiviral drug clevudine (CLV), which significantly reduces viral and antig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 47 publications
(78 reference statements)
5
26
0
Order By: Relevance
“…Similar data have emerged from other studies showing that woodchucks with chronic WHV infection were able to mount a strong antigen-specific immune response fol- lowing vaccination only after prolonged viremia reduction with potent antiviral drugs given for several months (19). Interestingly, we found that PBMCs from woodchucks with high viremia levels showed an impairment in the induction of IFN-␥ following stimulation with IL-12, while this alteration was not observed in animals with low viremia levels.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar data have emerged from other studies showing that woodchucks with chronic WHV infection were able to mount a strong antigen-specific immune response fol- lowing vaccination only after prolonged viremia reduction with potent antiviral drugs given for several months (19). Interestingly, we found that PBMCs from woodchucks with high viremia levels showed an impairment in the induction of IFN-␥ following stimulation with IL-12, while this alteration was not observed in animals with low viremia levels.…”
Section: Discussionsupporting
confidence: 90%
“…The presence of serum WHV surface antigen (WHsAg) levels was determined by enzyme-linked immunosorbent assay (ELISA) (2,19). The WHV e antigen (WHeAg) concentration was determined using a commercial ELISA for HBVe antigen that recognizes woodchuck antigen (DiaSorin S.p.A., Saluggia, Italy).…”
Section: Methodsmentioning
confidence: 99%
“…For determining T-cell responses against WHV, in vitro stimulators were used at concentrations previously determined as optimal for cultures of woodchuck peripheral blood mononuclear cells (PBMCs) (31,32). Viral antigen stimulators consisted of native 22-nm WHsAg (2 g/ml) and synthetic peptides of WHsAg and WHcAg.…”
Section: Methodsmentioning
confidence: 99%
“…Viral antigen stimulators consisted of native 22-nm WHsAg (2 g/ml) and synthetic peptides of WHsAg and WHcAg. WHs peptide S18 (10 g/ml; SigmaGenosys, The Woodlands, TX) corresponded to amino acids 341 to 360 of WHsAg starting at the N terminus of the large surface protein (32). WHc peptide C100-119 (10 g/ml; Sigma-Genosys) corresponded to amino acids 100 to 119 of WHcAg starting at the N terminus of WHcAg (31).…”
Section: Methodsmentioning
confidence: 99%
“…Most of the mice showed reduction of HBV DNA level and disappearance of HBeAg and HBsAg. Menne et al, 2007; A combination of conventional vaccine on the base of the WHV large surface protein contained HBsAg with pre-S and clevudine significantly restored the Tcell response to Pre-S and S region in chronic WHV infection. Miller at al, 2008; One hour post-infection with DHBV, DNA vaccine expressing DHBc and Pre-S/S and entecavir were given simultaneously and continued for 14 days.…”
Section: Immunotherapy For Viral Hepatitismentioning
confidence: 94%